Designing drugs that overcome antibacterial resistance: where do we stand and what should we do?. (June 2015) - Penchovsky, Robert; Traykovska, Martina
<x xml:space="preserve">Abstract</x> Introduction: In recent years, infections caused by multidrug-resistant bacterial pathogens have become a huge issue to public healthcare systems. Indeed, the misuse of antibiotics has led to, over the past 30 years, the emergence of a number of resistant bacterial strains including Staphylococcus aureus, Neisseria gonorrhoeae, Escherichia coli and Mycobacterium tuberculosis. Unfortunately, efforts to produce new antibiotics have not been sufficient to cope with the emergence of these new antibiotic-resistant (AR) strains. Areas covered: There is an urgent need to invent and employ unconventional strategies for antimicrobial drug development to tackle the rising global threats imposed by the spread of antimicrobial resistance. Herein, the authors discuss these novel design strategies and provide their expert perspective on the subject. Expert opinion: To deal with the growing threat of AR, it is important to cut down the use of antibiotics to the very minimum to diminish the risk of unknown drug-resistant bacteria and increase antibacterial vaccination programs. Furthermore, it is important to develop new classes of antibiotics that can deal with multidrug-resistant bacterial pathogens.